CLASSROOMINTERACTIONPATTERNS IN HIGHER EDUCATION - ningrum, Dini Setiana; Saleh, Mursid (English Education Journal, 2016)
This study was a classroom interaction analysis in English classes at Politeknik STTT Bandung. The classroom interaction was analyzed to find the patterns of classroom interaction. It is an observational research of TeknologidanBisnisGarmen students (S) and English teachers (T) in the 1st semester of Academic Year 2014/2015. The data were collected quantitatively with the Flandersâ Interaction Analysis Categories System. Then, the data findings were analyzed by interpreting them in order to find the patterns of classroom interaction. As the finding of this study, there were four basicpatterns of classroom interaction found in English classes at Politeknik STTT Bandung. They were (1) Teacher-Students (T â S), (2) Teacher-Student-Teacher (T â S â T), (3) Teacher-Student-Student (T â S â S), and (4) Student-Teacher (S â T) pattern. By using the interaction analysis, the writer could observe the patterns of classroom interaction, so the teacher would know the classroom atmosphere and develop his teaching skill and method. It was done in order to create the teaching and learning process more effective.